Building Sakinah family based on Islamic values of education - Ulfatmi; Jandra, Mifedwil; Ta’rif; M. Mujad; Zulpadrianto (Indonesian Journal of Islam and Muslim Societies, 2025)
This study examines the role of Islamic education in the formation of Sakinah families, focusing on the influence of Islamic values in marriage preparation and family life. The research aims to explore the factors contributing to the formation of Sakinah families in Padang, Indonesia, particularly the role of premarital education in fostering harmonious households. A qualitative approach was employed, involving purposive sampling of six Sakinah families and two families that experienced marital failure for comparative analysis. Data were collected through observations, interviews, and documentation, followed by a four-stage analytical process: orientation, exploration, data processing, and presentation of findings. The results reveal that Sakinah families prioritize religious and moral values in partner selection, legal and intentional marriages, and strong extended family support. Premarital education plays a crucial role in preparing individuals for marital responsibilities, enabling them to make informed decisions about their future spouses. The study highlights the significance of structured premarital education programs and recommends their integration into higher education curricula to equip students with essential knowledge for family life. This research contributes to the discourse on Islamic education and marital preparation by emphasizing the interplay between religious commitment, moral considerations, and premarital education in building stable and harmonious families. Penelitian ini mengkaji peran pendidikan Islam dalam pembentukan keluarga sakinah, dengan fokus pada pengaruh nilai-nilai Islam dalam persiapan pernikahan dan kehidupan keluarga. Penelitian ini bertujuan untuk mengeksplorasi faktor-faktor yang berkontribusi terhadap pembentukan keluarga Sakinah di Padang, Indonesia, khususnya peran pendidikan pranikah dalam membina rumah tangga yang harmonis. Pendekatan kualitatif digunakan, dengan menggunakan purposive sampling terhadap enam keluarga Sakinah dan dua keluarga yang mengalami kegagalan pernikahan untuk analisis komparatif. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi, diikuti dengan proses analisis empat tahap: orientasi, eksplorasi, pengolahan data, dan penyajian temuan. Hasil penelitian menunjukkan bahwa keluarga sakinah memprioritaskan nilai-nilai agama dan moral dalam pemilihan pasangan, pernikahan yang sah dan disengaja, serta dukungan keluarga besar yang kuat. Pendidikan pranikah memainkan peran penting dalam mempersiapkan individu untuk menghadapi tanggung jawab pernikahan, sehingga memungkinkan mereka untuk membuat keputusan yang tepat mengenai calon pasangan mereka. Penelitian ini menyoroti pentingnya program pendidikan pranikah yang terstruktur dan merekomendasikan pengintegrasian program tersebut ke dalam kurikulum pendidikan tinggi untuk membekali mahasiswa dengan pengetahuan yang esensial untuk kehidupan berkeluarga. Penelitian ini berkontribusi pada wacana pendidikan Islam dan persiapan pernikahan dengan menekankan interaksi antara komitmen agama, pertimbangan moral, dan pendidikan pranikah dalam membangun keluarga yang stabil dan harmonis.